Kontekstualisi Pemikiran Sayyed Hossein Nasr Tentang Pendidikan Islam - Akhsanudin, M. (Afkaruna: International Journal of Islamic Studies (AIJIS), 2024)
Contextualization of Sayyed Hossein Nasr's thoughts in the world of education is very important because it helps ensure that educational ideas and principles proposed by a thinker or figure can be applied effectively in different situations and environments. This research uses a library research approach with qualitative research methods. Sayyed Hossein Nasr is a prominent Islamic philosopher and scholar who was born in 1933 in Tehran, Iran. As a major figure in the Perennialism philosophical tradition, Nasr believed in the existence of eternal truths that underlie all religious traditions. He emphasized the concept of Scientia Sacra or "Sacred Science," which links knowledge to the spiritual dimension and God, and criticized the secular nature of modern science. Nasr also encouraged the Islamization of science, integrating Islamic principles in science to achieve spiritual awareness and manifest God's will in the world. His views play an important role in discussions about the relationship between religion and science in the Islamic world.